Desain Penggunaan Variable Frequency Drive (VFD) Pada Starting-Up Motor Induksi 3 Fasa Menggunakan Metode Sinusoidal Pulse-Width Modulation (SPWM) - Sumarta, Prima; Aini, Zulfatri (Universitas Al Azhar Indonesia, 2024)
During the start up process, the induction motor has a fairly high starting current. It can even reach four to eight times the motor's nominal current. An initial current that is large enough and repeated over a short period of time can cause quite high heat in the motor wire coils and trigger a current break. This occurs due to heat accumulating in the motor system. So repeated incidents within a short period of time can result in damage to the coils and other motor components. To overcome this, a Variable Frequency Drive (VFD) is used which works by periodically increasing the voltage frequency so that it is able to turn off the current at start-up time intervals or is called the Soft Starting method on motors. The VFD modeling design is carried out based on the SPWM topology with the output parameters of current rotation, THD and reactive power. Test results show that motor performance using a VFD is able to reduce current to 110% from previously 620%, reduce Total Harmonic Distortion (THD) from 5.01% to 3.54%, and reduce motor reactive load from 14.31 kVar to 8 kVar with capacitance value 121.78πF.Keywords – VFD, SPWM, Motor Starting, THD.